1996
DOI: 10.1002/jpln.1996.3581590502
|View full text |Cite
|
Sign up to set email alerts
|

Effect of potassium application on the transformation of zinc fractions in soil and on the zinc nutrition of wetland rice

Abstract: ZusammenfassungThe eNect of different levels of K application on the transformation of native as well as applied Zn fractions in a rice-growing soil was studied under two moisture regimes viz. waterlogged and alternate waterlogged and saturation. Application of K caused an increase in the water-soluble plus exchangeable. organically complexed and carbonates, and other acid-soluble mineral fractions of native soil Zn. Application of K also caused an increase in the transformation of applied Zn into all the abov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…Both increased soluble plus exchangeable and decreased weakly specifically adsorbed metals may be due to the competitive exchange between K and heavy metal ions on soil solids. The results of this study are in agreement with the findings of Mandal et al (12), who reported that addition of K at 25 -50 mg K kg Ϫ1 increased Zn in the soluble plus exchangeable fraction.…”
Section: Effect Of Added Potassium On Heavy Metal Distributionsupporting
confidence: 95%
See 1 more Smart Citation
“…Both increased soluble plus exchangeable and decreased weakly specifically adsorbed metals may be due to the competitive exchange between K and heavy metal ions on soil solids. The results of this study are in agreement with the findings of Mandal et al (12), who reported that addition of K at 25 -50 mg K kg Ϫ1 increased Zn in the soluble plus exchangeable fraction.…”
Section: Effect Of Added Potassium On Heavy Metal Distributionsupporting
confidence: 95%
“…Phosphorus addition was found to cause a reduction in the water soluble plus exchangeable and an increase in the amorphous and crystalline sequioxide bound fractions of zinc (11). Application of K can increase the water soluble plus exchangeable, organically complexed and carbonate fractions of soil Zn (12).…”
Section: Introductionmentioning
confidence: 96%
“…Soil solution thermodynamic findings for Zn behaviour in flooded soils showed soluble P was the most effective in Zn immobilization through lower soluble Zn products formation (Mandal and Mandal 1990;Rupa et al 2003).…”
Section: Water Soluble Plus Exchangeable Zinc Fractionmentioning
confidence: 99%
“…On the other hand, formation of Fe 2+ and Mn 2+ in soil under the flooded condition, compete with Zn 2+ for exchange sites and thus restricts the entry of applied Zn into the exchange complexes sites. The increase in soluble Fe 2+ and Mn 2+ may also displace some of the Zn that already present in the exchange complex leading to its reaction with P in the solution phase with formation of compounds with lower solubility (Mandal and Mandal 1990;Shuman 1985;Shuman 1998).…”
Section: Water Soluble Plus Exchangeable Zinc Fractionmentioning
confidence: 99%
See 1 more Smart Citation